Innovation of E-Learning Based Google Site on Islamic Lesson For High School Students an Effort To Facilitate Self-Control - Farida Saifulloh; Sudiyanto Sudiyanto; Mohammad Muchtatom (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The national education system needs to develop a more innovative learning system in order to improve the ability of graduates with 21st-century skills. Contrarily, the lack of educational media development in Islamic education lowers student interest in studying, which has an impact on academic performance and self-control. This study aims to develop an e-learning-based Google Sites media in Islamic Lesson for High School Students. This research was a type of Research and Development (R&D) using the Alessi and Trollip development model, which consists of 3 stages; planning, design, and development. The research subjects were 33 students and 2 teachers. Data were collected using questionnaires, tests, and interview guidelines. The data collection instrument uses a questionnaire sheet. Data analysis techniques using qualitative and quantitative descriptive analysis. The research results showed that two media experts gave an average score of 3.48, two material experts gave an average score of 3.63, and two instructional design experts gave a score of 3.74. It was concluded that e-learning-based Google Sites media were declared valid and feasible. E-learning-based Google Site media can be used in Islamic Lessons at once to facilitate self-control student of High School students.